Creation and implementation of a last generation English Laboratory for the last third students courses at Abdón Calderon Military High School in Quito, during the two first trimesters - Morales Garrido, Nelson Ricardo (2006)
Considering the last trends in the field of the teaching English language are focuses on the use of modern and effective techniques and equipments which permit students to reach an excellent percentage in the learning English as a second language, it is necessary for us to make use of these modern teaching tools which can be implanted in advanced language laboratories. So we knew that the Abdón Calderón Military High School has an old fashion language laboratory which is difficult to use due to the lack of modern advanced technology that permits teachers to enhance the action and control field, likewise the students improve their language learning ratio, for reasons like that, it is mandatory for us to develop a new study in order to get a new and last generation laboratory in this institution. The aim of our study is to reinforce the teachers and students knowledge, taking advantages in the use of modern techniques such as: English on line through internet, multimedia courses in CDs, tape recorders and news in English. This project, which will help teachers and students to fulfill their goals and get satisfy in the teaching-learning process by means of the use of advanced equipment and programs...